Evaluation of sweet sorghum (Sorghum bicolor) genotypes for biomass, sugar and ethanol production under different levels of nitrogen - MIRI, KHALED; RANA, D S (The Indian Journal of Agricultural Sciences, 2012)
Sweet sorghum [Sorghum bicolor (L.).Moench] stalks contain high fermentable sugar and thus have potential to produce bio-ethanol along with grains and crushed dry matter. Its cultivars differ in production potential, adaptation, duration and response to nitrogen level under different agro-climatic conditions. A field experiment was conducted at New Delhi, during kharif season of 2009 and 2010 to evaluate three sweet sorghum genotypes (varieties: RSSV 9, SSV 84, and hybrid: CSH 22 SS) under four nitrogen levels (0, 50, 100 and 150 kg N/ha for growth, biomass, fermentable sugar and potential ethanol yield. In the first year, except green biomass, juice yield, fermentable sugar yield and expected ethanol yield recorded significant increase up to 100 kg N/ha, while green biomass yield responded up to 150 kg N/ha. In the second year, all yield parameters except brix (%) showed marked improvement up to 150 kg N/ha. Expected ethanol yield recorded 83.4% and 77.7% increase due to application of 150 kg N/ha over control in 2009 and 2010 respectively. Among the genotypes, hybrid CSH 22 SS showed it’s significant superiority in the above mentioned yield parameters over varieties, except brix (%), which was the highest in RSSV 9. Hybrid CSH 22 SS recorded 112% and 34% increase in ethanol yield over SSV 84 and RSSV 9, respectively. Interaction effect of nitrogen × genotypes for all above characters, except brix (%) was significant. Hybrid CSH 22 SS responded significantly up to 150 kg N/ha, while in case of varieties response to N application was significant only up to 100 kg N/ha. Net return with 150 kg N/ha fertilizer application recorded 116.9 and 116.3% increase over control in 2009 and 2010 respectively. On an average hybrid CSH 22 SS produced net returns of ` 41 540 which was 135 and 41% higher than SSV 84 and RSSV 9 respectively.